The Nurse's Tale: Other Worlds and Parallel Worlds in the Exposition of Euripides' Hypsipyle. (2019) - Chong-Gossard, James H. K. O.
Abstract: This article analyses Euripides' mythopoetics in what survives of the first quarter of his fragmentary Hypsipyle: prologue, parodos, and first episode. It examines Euripides' innovation in joining two myths (the Seven Against Thebes and the story of Hypsipyle and the Argonauts) into one, and the representation of Hypsipyle herself. In her private moments, the thoughts that preoccupy her mind are focused on other-places and other-times, in vivid contrast to the naturalistically presented world of the present where, as a slave, she must interact with men. Euripides uses the language of serving (θɛραπɛύɛιν) and doing a 'favour' (χάρις), as well as the word ἐρῆμος ('lonely, ' 'deserted') and homoeophonic language (e.g. Argo and Argos) to indicate that, in helping the Argives, Hypsipyle repeats typologically her hospitality to the Argonauts. There is a circularity in Hypsipyle's story that creates suspense, since by doing a favour for the Argive leader, she is reunited with the sons she bore to Argonauts' leader, who themselves are sent to find her by their grandfather whom she saved; and by losing the infant in her care (Opheltes, later named Archemorus), she is reunited with her former infants. By the end of Hypsipyle's first conversation with Amphiaraus, Euripides has invented a theme of 'parallel worlds' that he will resolve at the play's end.